KEANEKARAGAMAN JENIS MAMALIA DI TAMAN NASIONAL SEBANGAU, KALIMANTAN TENGAH - Abdul Haris Mustari; Hadi Surono; Diena Nur Fatimah; Agus Setiawan; Riema Febria (Media Konservasi, 2010)
Sebangau National Park located in central Kalimantan is the largest peat swamp ecosystem on the island.  The national park is habitat of  many wildlife  species that have been adapted with the unique yet fragile ecosystem, peat swamp forest.   Mammals  species plays important role in ecosystem especially for forest regeneration; the animals are agents for seeds distribution and keep the forest healty and ecologically function.   This study aimed to reveal mammals biodiversity in the national park, that was conducted in August 2010.  A total of 46 species of mammals recorded during the study,  and 37 of the species encountered have been  protected by Indonesian Government Regulation No.7 of 1999, and are listed as endangered species by the IUCN such as orang utan and gibbon. Keywords: mammals, diversity, Sebangau National Park.